The Effect of Leadership, Motivation and Job Satisfaction on Employee Performance of PT. Pos Indonesia Lamongan Branch - Kartikasari Kartikasari; Abid Muhtarom; Mohammad Yaskun (Jurnal Multidisiplin Sahombu, 2025)
This research was conducted at PT. Lamongan Branch Post. In its implementation, there are still several problems related to providing motivation and the application of leadership that cause the company's organizational system to not run optimally. Every employee is expected to have a high level of awareness of themselves and the work environment, but in reality not all employees are able to comply with regulations and show maximum work awareness. This study aims to determine the influence of leadership, motivation, and job satisfaction on employee performance at PT. Lamongan Branch Post. The research method uses a quantitative approach with research instruments in the form of questionnaires distributed to employees of PT. Lamongan Branch Post as a respondent. Based on the results of the t-test, it was obtained that the leadership variable (X1) had a calculated t-value of 3.985, the motivation variable (X2) of 3.079, and the work satisfaction variable (X3) of 2.936. All of these calculated t-values are greater than the table t-values of 1.987 so H0 is rejected and H1 is accepted. This shows that partially the variables of leadership, motivation, and job satisfaction have a positive and significant effect on employee performance (Y) at PT. Lamongan Branch Post. Simultaneously, the variables of leadership, motivation, and job satisfaction have also been shown to affect employee performance. This is shown from the results of the F test with an F value of 8.918 which is greater than the F of the table of 3.10 and a significance level of 0.000 which is smaller than 0.05. The results of multiple linear regression analysis resulted in the equation Y = 7.761 + 0.468X1 + 0.266X2 + 0.117X3. Based on the value of the beta coefficient (β), the leadership variable (X1) has the greatest value compared to other variables so that it is stated as the most dominant variable affecting employee performance (Y) at PT. Lamongan Branch Post. Thus, it can be concluded that improving the quality of leadership will have a greater influence on improving employee performance than motivation and job satisfaction.